Vision Loss After Prone Spinal Surgery in a 38-Year-Old Woman: Implications for Perioperative Nursing Practice - Asep Ermaya; Tuti Pahria; Melly Rahmayani; Khornelius Ryan Aprilliano (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Prone positioning in spine surgery improves surgical exposure but is associated with significant ocular, neurologic, and pressure-related risks. Central retinal artery occlusion (CRAO) is a rare yet devastating complication linked to compromised ocular perfusion during prone procedures. Prolonged prone positioning also increases the risk of perioperative pressure injuries due to sustained external pressure and immobility. Perioperative nurses play a crucial role in risk identification, safe positioning, pressure injury prevention, and early recognition of adverse events to minimize irreversible complications. This case report describes a 38-year-old woman who underwent cervical spine surgery in the prone position and developed sudden painless unilateral vision loss accompanied by incomplete cranial nerve palsies postoperatively. Perioperative nursing interventions focused on comprehensive risk stratification, safe prone positioning with appropriate padding and eye protection, prevention of pressure-related tissue injury, close hemodynamic monitoring, and targeted postoperative visual and skin integrity assessments. Despite prompt multidisciplinary management, visual recovery remained limited. This case highlights the importance of evidence-based perioperative nursing practices in reducing prone position–related ocular and pressure injuries, supports the implementation of standardized positioning and pressure injury prevention protocols, and underscores the need for continuous vigilance in perioperative clinical practice. Keywords: perioperative nursing; prone position; cervical spine surgery; postoperative visual loss; pressure injury prevention